ORGANIZATIONAL STRUCTURE OF INTERNAL AUDIT AND REQUIREMENTS FOR AUDIT ACTIVITY - Karaev Payzillakhon Yusufxonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Internal audit is one of the ways of regulating the activity of the economic entity, but its distinguishing feature is the possibility of representing the business entity as part of the management (control), and on the part of economic activity (financial and economic activities). Properly organized internal audit service will give the organization the benefits and serve as a guarantor of increasing profits.